Optimization Approach for Kinetics Parameters Determination for Oil Palm Waste Steam Gasification with In-Situ CO2 Capture for Hydrogen Production - Inayat, Abrar (2011)
Biomass steam gasification with in-situ carbon dioxide capture using CaO exhibits good prospects for the production of hydrogen rich gas. The present work focused on the determination of reaction rate kinetics for hydrogen production from oil palm waste steam gasification using optimization approach in MATLAB. The kinetics parameters were calculated by fitting experimental data to kinetics model and minimization of least squared error between the model predictions and experimental results. The model was validated and showed good agreement with the literature. The developed model was used to investigate the effect of temperature and steam/biomass ratio on the product gas composition. Based on the results, hydrogen purity of more than 70 mol% can be achieved. It was found that increment in temperature and steam/biomass ratio is in favor of hydrogen production. The study provided a useful optimization approach for the determination of kinetics parameters for a specific biomass in future experimental work.